2020
DOI: 10.1371/journal.pone.0228741
|View full text |Cite
|
Sign up to set email alerts
|

Doppler evaluation of renal resistivity index in healthy conscious horses and donkeys

Abstract: The renal resistive index (RRI) is used as a measurement of downstream resistance in arteries. The aim of this study was to assess the RRI of the arcuate arteries by pulsed-wave Doppler ultrasonography in healthy conscious horses and donkeys, and to verify any differences related to age, breed, bodyweight (BW) or body condition (BCS). Thirty-three healthy conscious horses and nine donkeys had their systolic and diastolic flow velocities at the level of the arcuate arteries estimated by pulsed-wave Doppler ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 30 publications
3
27
1
Order By: Relevance
“…Renal RI is influenced by numerous hemodynamic and physiological factors such as vascular compliance, different pressures (pulse, urethra, intra-abdominal) and plasma renin activity [ 16 ]. The RI values obtained in the present study were within the range of reference values reported for healthy adult humans [ 11 ], dogs and cats [ 10 , 12 ], and horses and donkeys [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Renal RI is influenced by numerous hemodynamic and physiological factors such as vascular compliance, different pressures (pulse, urethra, intra-abdominal) and plasma renin activity [ 16 ]. The RI values obtained in the present study were within the range of reference values reported for healthy adult humans [ 11 ], dogs and cats [ 10 , 12 ], and horses and donkeys [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 84%
“…Age, sex and body weight (BW) have been studied as potential factors influencing the RI in humans [ 11 , 19 ], dogs [ 20 ], cats [ 9 , 23 ], horses and donkeys [ 24 , 25 ]. Although sex has not been identified as an influential factor in any species, age [ 11 , 20 ] and BW can alter the RI [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Tipisca et al [4] reported significantly higher RI values in the left than right kidneys in healthy cats. In horses, the RI in the right kidney was statistically higher than in the left kidney [13]. These authors reported that different RI values between both kidneys is difficult to explain.…”
Section: Discussionmentioning
confidence: 90%
“…These authors reported that different RI values between both kidneys is difficult to explain. Unless there were any microscopical differences in functional subunits which are not known, or technical factors, since ultrasonography is essentially an operator-dependent method [4,13].…”
Section: Discussionmentioning
confidence: 99%